2013
DOI: 10.3892/mmr.2013.1315
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine protects against myocardial injury via inhibition of JAK2/STAT3 signaling in rat septic shock

Abstract: Oxymatrine (OMT), an alkaloid extracted from Sophora japonica (kushen), is used to treat inflammatory diseases and various types of cancer in traditional Chinese medicine. However, the cellular and molecular mechanisms underlying the anti‑inflammatory activity of OMT remain poorly understood. The present study explored the protective effect of OMT on myocardial injury in rats with septic shock by inhibiting the activation of the janus kinase‑signal transducer and activator of transcription (JAK/STAT) signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…In spontaneously hypertensive rats, oxymatrine prevents ventricular remodeling, myocardial hypertrophy, and cardiac fibrosis [12]. Oxymatrine also exhibits anti-inflammatory activity, which protects against myocardial injury in septic shock [14]. The protective effect of oxymatrine on aldosterone-induced myocardial injury has been shown to be similar to the effect of spironolactone, a competitive aldosterone inhibitor [13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In spontaneously hypertensive rats, oxymatrine prevents ventricular remodeling, myocardial hypertrophy, and cardiac fibrosis [12]. Oxymatrine also exhibits anti-inflammatory activity, which protects against myocardial injury in septic shock [14]. The protective effect of oxymatrine on aldosterone-induced myocardial injury has been shown to be similar to the effect of spironolactone, a competitive aldosterone inhibitor [13].…”
Section: Discussionmentioning
confidence: 96%
“…Its anti-oxidative activity has been useful in the treatment of liver fibrosis, viral hepatitis, skin diseases, and autoimmune disease [8]. Recently, oxymatrine has been extensively studied for its protective effects against heart injuries induced by isoproterenol [9], myocardial ischemia [10, 11], hypertension [12], aldosterone [13], septic shock [14], and arrhythmias [15]. However, the effects of oxymatrine on doxorubicin-induced cardiotoxicity have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al found that the increased levels of the TNF‐α and IL‐1β proteins induced by cecal ligation and puncture and the cardiac muscle injury induced by septic shock were markedly attenuated by OM treatment in a dose‐dependent manner in rats. The edema, degeneration, and necrosis of the myocardial tissues were significantly reduced following the administration of OM, which has been found to parallel the levels of the JAK2 and STAT3 proteins (Zhang et al , ). Similarly, Wang et al found that the levels of TNF‐α and IL‐1β in renal tissue were decreased following administration with OM in a rat model of septic shock.…”
Section: Introductionmentioning
confidence: 85%
“…1). It has been used for the treatment of inflammatory diseases, various types of cancer, heart injury induced by myocardial ischemia [11], hypertension [12], and septic shock [13], and previous studies have shown that it is effective against ischemia and reperfusion injury [14]. The effective mechanisms may be the inhibition of oxidative stress, inflammation, and induction of apoptosis.…”
Section: Introductionmentioning
confidence: 99%